Validity, Practicality, Effectiveness: Wetland Contexted-Chemical Representation Module as a Media for Learning - Almubarak Almubarak; Parham Saadi (Universitas Lambung Mangkurat, 2022)
where it consists of 3 (three) levels, namely macroscopic, particulate, and symbolic. Learning resources with environmental integration and representation concepts are chemical learning media that can strengthen their understanding of learning. However, the chemistry teacher has not been judged to successfully achieve the essence of learning in the science aspect. This study aimed to analyze a chemical representation module contexted-wetland by three aspects (validity, practicality, effectivity). The Plomp Development Model was the research method chosen, but research content focused on to validity, practicality, and effectiveness of product. Especially in effecttiveness, the result also showed how students’ understanding to the chemistry and the wetland perspective. Technique, observation, and documentation were the collecting techniques used; Rasch modeling and descriptive statistics used were to find out the symptoms of the data, which was data interpretation; Rasch modeling result was as a preliminary stage in research, then doing others stage (developing context). The finding revealed that the Rasch modeling result demonstrated that person reliability is weak, so it showed that teachers needed to design learning that is suitable and according to student learning needs (preliminary stage). Furthermore, the chemical representation module contexted-wetland assessed worthy (valid, practice, effective) for use in class as a media for learning. The conclusion is developing the media for learning, especially integrating the wetland as local wisdom, chemical representation, and other things that can increase the number of college students because they, college students, are the future. Additionally, this research can be a new reference for teachers in designing instructional media in chemistry learning